Study of Variations in the Extraction Yield, Phenolic Contents and Antioxidant Activities of the Bark of F. religiosa as a Function of Extraction Procedure - Aftab Ashraf; Ijaz Ahmad Bhatti; Bushra Sultana; Amer Jamil (Journal of Basic & Applied Sciences, 2016)
In present study, the effect of different solvents and multiple techniques on the extraction yield, phenolic contents and antioxidant activities of bark of F. Religiosa, was investigated. Four solvents (absolute ethanol, absolute methanol, 80% aqueous ethanol and 80% aqueous methanol) and three techniques (orbital shaker, sonication and magnetic stirrer) were applied for this purpose. The extract obtained by the application of 80% methanol, exhibited significantly (p<0.05) higher antioxidant activities. The statistical order of the solvents according to their efficiency was 80% methanol > 80% ethanol > absolute methanol >absolute ethanol. As for as techniques are concerned, the extracts obtained by the application of sonication demonstrated significantly (p<0.05) higher antioxidant activities as compared to to the extracts obtained as a result of using magnetic stirrer and orbital shaker.